Sedimentary and faunal signatures of the post-glacial marine drowning of the Pontocaspian Gemlik “lake” (Sea of Marmara) - Taviani, M.; Angeletti, L.; Cagatay, M. N.; Gasperini, L.; Polonia, A.; Wesselingh, F. P. (Quaternary International, 2014)
A Late Pleistocene (Neoeuxinian) Pontocaspian fauna is documented from sediments cored at̴ ∼75 m present water depth in the shallow-silled (∼50 m) Gulf of Gemlik, Sea of Marmara. As determined by AMS-14C dating of Pontocaspian gastropods (15,860 ± 90 BP uncal.), the age of such fauna is consistent with known episodes of Caspian overflow into the Black Sea Basin (Early Hvalynian floods). The fossil mollusc fauna is relatively diverse (12 non-marine taxa), made up of neritid and hydrobioid gastropods, and dreissenid and lymnocardiine bivalves. The presence of hitherto poorly known Pontocaspian taxa in the Sea of Marmara, further documented by the record in Gulf of Gemlik, seems to document that the Neoeuxinian Sea extended south of the Bosporus in the latest Pleistocene. Further, they provide insight into the origin of the modern Black Sea Pontocaspian taxa. The Gemlik Neoeuxinian lacustrine-brackish fauna under scrutiny is the westernmost known expansion of the Pontocaspian domain during the Late Pleistocene. This distinct biogeographic faunal affinity, with all its eastbound implications in terms of landscape and seaway connections, came to an end with the abrupt marine inundation that accompanied the postglacial sea-level rise from the Mediterranean Sea.